The effects of interactive video games combined with LEGO game therapy on social anxiety in rural left-behind children - Peng, Dianhui; Wu, Xinbo; Yang, Yaqi; Li, Xiaolin; Shu, Anni; Liang, Junwen; Tu, Zengying; Liu, Le; Yang, Qian; Dong, Weixin; Lu, Chunxia (Frontiers in Psychology, 2024)
BackgroundChina has a significant population of left-behind children, defined as those whose parents have migrated away from their home for at least six months. This situation arises when one or both parents leave to seek work in urban areas. Among the various challenges faced by left-behind children, social anxiety has emerged as one of the most pressing issues.ObjectiveThis study aims to deeply explore the impact of interactive video games and LEGO games on the social anxiety of rural left-behind children, with the aim of providing a more comprehensive and effective solution to the mental health problems they encounter.MethodsEighty-four rural left-behind children were randomly assigned to four groups: interactive video game group, LEGO game group, combined intervention group, and the control group, using a single-blind randomized controlled experiment. All participants underwent the intervention three times a week for 12 weeks. Social anxiety levels were assessed at three points: before the intervention (T0), immediately after the intervention (T1), and 6 weeks post-intervention (T2).ResultsThe effects of different intervention strategies on the social anxiety of left-behind children showed significant group-time interaction effects. As the intervention progressed, the total score of social anxiety and the scores of various dimensions among participants in different intervention groups showed a gradual decreasing trend. The combined intervention group scored significantly lower at T1 and T2 than both the interactive video game group and the LEGO group.ConclusionOur findings indicate that social anxiety in left-behind children can be significantly mitigated through both LEGO therapy and interactive video games, with a combined approach yielding the most pronounced effects. These results underscore the importance of a multifaceted intervention strategy that addresses the unique social needs of this vulnerable population. Importantly, our study suggests that effective interventions should not only focus on symptom reduction but also foster environments that enhance social skills and build confidence. Future research should investigate the scalability of these interventions across diverse contexts and their potential integration into existing mental health services to better support left-behind children.